Video transmission over wireless networks review and recent advances - Ahmed, Diaa Eldein Mustafa; Khalifa, Othman Omran; Jama, Abdirisaq M. (Association of Technology and Science, India, 2015)
Video transmission over wireless networks is considered the most interesting application in our daily life nowadays. As mobile data rates continue to increase and more people rely on wireless transmission, the amount of video transmitted over at least one wireless hop will likely continue to increase. This kind of application needs large bandwidth, efficient routing protocols, and content delivery methods to provide smooth video playback to the receivers. Current generation wireless networks are likely to operate on internet technology combined with various access technologies. Achieving effective bandwidth aggregation in wireless environments raises several challenges related to deployment, link heterogeneity, Network congestion, network fluctuation, and energy consumption. In this work, an overview of technical challenges of over wireless networks is presented. A survey of wireless networks in recent video transmission schemes is introduced. Demonstration results of few scenarios are showed.